LncRNA TUG1 promotes hypertrophic scar formation via the miR-627/IGF1R axis - Zeming Bai; Ziyang Han; Xiangzi Kong; Rirui Zhao; Haiwei Sun; Hai Huang; GuYue Wang; Zhe Li; Kai Tao; Jiulong Liang (Journal of Molecular Histology, 2026)
Hypertrophic scars (HS) are fibrotic skin disorders driven by abnormal fibroblast activity. The molecular mechanisms underlying HS remain incompletely understood, particularly the role of non-coding RNAs. Expression levels of lncRNA TUG1, miR-627, and IGF1R were measured in HS tissues and fibroblasts using qRT-PCR and Western blotting. Dual-luciferase assays validated direct interactions. Functional effects of TUG1 and miR-627 on fibroblast proliferation and migration were assessed using MTT and Transwell assays. A rabbit ear model of HS was used to examine in vivo effects of TUG1 and miR-627 modulation on scar formation and molecular expression. TUG1 was significantly upregulated in HS tissues and inversely correlated with miR-627, which was downregulated. TUG1 promoted fibroblast proliferation and migration by directly sponging miR-627, thereby lifting repression on IGF1R, a known pro-fibrotic effector. Luciferase assays confirmed direct binding of miR-627 to both TUG1 and IGF1R. Co-transfection of miR-627 attenuated TUG1-induced IGF1R upregulation and reversed its pro-fibrotic cellular effects. In vivo, TUG1 overexpression led to increased scar thickness, collagen deposition, and IGF1R expression, while miR-627 overexpression mitigated these effects. Co-administration of both restored scar morphology and molecular markers to near-control levels. TUG1 promotes hypertrophic scar formation by sponging miR-627 and derepressing IGF1R. This newly identified TUG1–miR-627–IGF1R axis plays a central role in HS pathogenesis and may serve as a promising therapeutic target for fibrotic skin disease.

Dynamic mesh-based investigation of thermal environment during mars ascent vehicle launch phase - Zhongyi Sun; Zhanxun Che; Chengeng Zhao; Zeming Wang; Guigao Le (Advances in Space Research, 2026)

Study on the pro-inflammatory mechanism mediated by the RANK-SPP1 axis in macrophage immunomodulation during atherosclerosis - Qiyu Sun; Yanbo Hu; Zeming Sun; Mingyan Shang; Zhengyi Li; Juan Shen; Zhenzhen Cui; Jiaxin Yang; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2026)

Performance study on a cryogenic bubble pump for low-flow-rate liquid nitrogen transfer - Yuhui Chen; Ya Xu; Daming Sun; Zeming Wang; Qie Shen (International Journal of Refrigeration, 2026)

Fouling in beer clarification using polyethersulfone hollow fiber membranes - Hui Ye; Zeming Yan; Leiming Lou; Jie Sun; Junhui Zhong; Lei Zhang; Peng Liu; Zhonghou Feng (Journal of Food Engineering, 2026)

Ethanol-induced stable dispersion and compatibility of MXene in WEP leading to highly ordered layered materials for high electromagnetic interference shielding performance - Yingfan Li; Bohan Ding; Xiaoyan Ma; Yongjie Bi; Zeming Jin; Yue Sun; Jinghe Guo; Yanxiang Wang; Chao Teng (Chemical Engineering Journal, 2026)

Towards coordinated sustainability: A systematic study of cross-regional synergy in pollution reduction and CO2 mitigation in the Dongjiang River Basin - Yongxi Sun; Yulei Xie; Jinhui Hu; Qitao Rao; Zeming Chen (Journal of Environmental Management, 2025)

Editorial: Environmental behavior processes and mechanisms of organic pollutants in global coastal waters - Kai Zhang; Omowunmi H. Fred-Ahmadu; Yuxin Sun; Hong-Hai Zhang; Zeming Zhang (Frontiers in Marine Science, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Co-exposure to enrofloxacin and atrazine enhances the hepatotoxicity in Larimichthys crocea by targeting the hypothalamic–pituitary–thyroid and gut–liver axes - Yinan Wang; Chenxue Yang; Qiangqiang Shi; Liuquan Zhang; Hao Liu; Jinjie You; Rongrong Zhang; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2025)

Effects of elevated CO2 concentration on Se accumulation and associated rhizobacterial community in Cardamine hupingshanensis - Huawei Zang; Wenyao Shi; Minyi Kau; Jiayuan Li; Jinxing Li; Wanying Zhang; Zeming Zhou; Bowen Sun; Linxi Yuan; Renbin Zhu (Plant and Soil, 2025)

Accumulation patterns and chronic toxic effects of triphenyl phosphine in Mytilus coruscus - Ningbo Wang; Yinan Wang; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Combined ecotoxicity of polystyrene microplastics and Di-(2-ethylhexyl) phthalate increase exposure risks to Mytilus coruscus based on the bioaccumulation, oxidative stress, metabolic profiles, and nutritional interferences - Yinan Wang; Qiangqiang Shi; Menglan Zhang; Lingyan Xu; Qiang Wei; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Accumulation and growth toxicity mechanisms of fluxapyroxad revealed by physiological, hepatopancreas transcriptome, and gut microbiome analysis in Pacific white shrimp (Litopenaeus vannamei) - Ningbo Wang; Rongrong Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Unveiling the hidden risks: Pesticide residues in aquaculture systems - Weijia Gan; Rongrong Zhang; Zhi Cao; Hao Liu; Wentao Fan; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Effects of coal-fired power plants on soil microbial diversity and community structures - Bowen Sun; Renbin Zhu; Yu Shi; Wanying Zhang; Zeming Zhou; Dawei Ma; Runfang Wang; Haitao Dai; Chenshuai Che (Journal of Environmental Sciences, 2024)

Comparative antioxidant and metabolomic analysis for the identification of differential response of mussel (Mytilus coruscus) to four succinate dehydrogenase inhibitor fungicides - Ningbo Wang; Zeming Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Hua Liu; Xizhi Shi (Environmental Science and Pollution Research, 2024)

Accumulation and elimination properties and comparative toxicity of fluxapyroxad in juvenile and adult large yellow croaker (Larimichthys crocea) - Ningbo Wang; Yinan Wang; Aili Sun; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Chain-mediating effect of interaction between telomeres and mitochondria under oxidative stress in coke oven workers - Zhiguang Gu; Zeming Niu; Zhaofan Yan; Yahui Fan; Jing Sun; Xiangkai Zhao; Xiaoran Duan; Wu Yao; Yongli Yang; Wei Wang (Environmental Pollution, 2023)

Bioinspired rapid self-replenishing liquid-infused surfaces for stable anti-adhesion of electrosurgical electrodes - Zeming Li; Wenshuai Wu; Jiayu Sun; Jiteng Li; Deyuan Zhang (Chemical Engineering Journal, 2023)

Illumination Adaptive Multi-Scale Water Surface Object Detection with Intrinsic Decomposition Augmentation - Zhiguo Zhou; Zeming Li; Jiaen Sun; Limei Xu; Xuehua Zhou (Journal of Marine Science and Engineering, 2023)
Visual object detection is an essential task for the intelligent navigation of an Unmanned Surface Vehicle (USV), which can sense the obstacles while navigating. However, the harsh illumination conditions and large scale variation of the objects significantly harm the performance of object detection methods. To address the above problems, we propose a robust water surface object detection method named multi-scale feature fusion network with intrinsic decomposition generative adversarial network data augmentation (MFFDet-IDGAN). We introduce intrinsic decomposition as data augmentation for the object detection to achieve illumination adapting. And an intrinsic decomposition generative adversarial network (IDGAN) is proposed to achieve unsupervised intrinsic decomposition. Moreover, the multi-scale feature fusion network (MFFDet) adopts an improved bidirectional feature pyramid network (BiFPN) and spatial pyramid pooling (SPP) blocks to fuse features of different resolution for better multi-scale detection. And an improved weighted stochastic weight averaging (SWA) is proposed and applied in the training process to improve the generalization performance. We conduct extensive experiments on the Water Surface Object Detection Dataset (WSODD), and the results show that the proposed method can achieve 44% improvement over the baseline. And we further test our method on a real USV in the sailing process, the results show that our method can exceeding the baseline by 4.5%.

Simultaneous determination and dietary intake risk assessment of 60 herbicide residues in aquatic products - Xinru Yu; Feng Xu; Rongrong Zhang; Hua Liu; Aili Sun; Liuquan Zhang; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Environmental profile, potential sources, and ecological risk of polycyclic aromatic hydrocarbons in a typical coastal bay and outer bay area - Yuyao Wu; Zeming Zhang; Wei Huang; Hua Liu; Rongrong Zhang; Haifeng Jiao; Aili Sun; Jiong Chen; Xizhi Shi (Environmental Science and Pollution Research, 2023)

Urban trees in university campus: structure, function, and ecological values - Xueyan Wang; Yanlin Wang; Xiaohan Qu; Bing Huang; Zeming Li; Junjiao Sun; Xiaoqing Wei; Xiuying Yang (Environmental Science and Pollution Research, 2021)

Pharmacokinetics of the main compounds absorbed into blood after oral administration of Liu Wei Di Huang Wan, a typical combinatorial intervention of Chinese medical formula - Ning Zhang; Lijing Li; Ping Wang; Hui Sun; Zeming Wu; Chengyu Piao; Xijun Wang (Journal of Natural Medicines, 2013)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Natural and experimental constraints on formation of the continental crust based on niobium–tantalum fractionation - Xing Ding; Craig Lundstrom; Fang Huang; Jie Li; Zeming Zhang; Xiaoming Sun; Jinlong Liang; Weidong Sun (International Geology Review, 2009)